1995
DOI: 10.1002/mc.2940120207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the liver‐enriched transcription factors C/EBPα, C/EBPβ, HNF‐1, and HNF‐4 in preneoplastic nodules and hepatocellular carcinoma in rat liver

Abstract: The expression patterns of the liver-enriched transcription factors CCAAT/enhancer-binding protein (C/EBP) alpha and beta and hepatocyte nuclear factor (HNF)-1 and HNF-4 were studied in liver nodules and hepatocellular carcinomas from male rats treated according to the resistant hepatocyte (RH) model. C/EBP alpha expression was lower at the transcriptional, mRNA, and protein levels in persistent nodules than in the respective surrounding livers. Expression was further decreased in the tumors. Transcriptional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 46 publications
(12 reference statements)
0
26
0
Order By: Relevance
“…One of the central mediators in this regulatory network is HNF4α, which regulates not only the hepatocyte proliferation and differentiation but also the hepatic epithelial morphology (12). Previous studies clarified that the expression of HNF4α was decreased in rodent and human HCC in comparison with the adjacent noncancerous tissues (21)(22)(23). With this study, we reported the progressive reduction of HNF4α during hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the central mediators in this regulatory network is HNF4α, which regulates not only the hepatocyte proliferation and differentiation but also the hepatic epithelial morphology (12). Previous studies clarified that the expression of HNF4α was decreased in rodent and human HCC in comparison with the adjacent noncancerous tissues (21)(22)(23). With this study, we reported the progressive reduction of HNF4α during hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] It has also been recognized that LETFs play important roles in liver differentiation, which is strictly controlled by the appropriate LETF expression pattern at each embryonic developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcriptional alterations of these factors were observed between normal tissues and preneoplastic nodules or cancerous tissue taken from the same subject, both in clinical samples 8) and in chemically induced tumors of mice. 9,10) These reports suggest that changes of LETFs expression occur in hepatocarcinogenesis and their pattern and extent reflect the characteristics of HCCs, especially the differentiation grade. However, little is known about the correlation between histological differentiation and HNF-1α and HNF-1β, 11) and no study has as yet clarified the correlation between the expression of LETFs mRNAs and differentiation at the level of functional protein expression in HCCs.…”
mentioning
confidence: 97%
“…Many studies have shown that C/EBP␣ can induce cell growth arrest in various cell types. For example, C/EBP␣ expression is reduced in preneoplastic nodules compared with the surrounding liver tissues (43). C/EBP␣ overexpression inhibits hepatocyte proliferation and also suppresses colony growth in mouse fibroblasts (44,45).…”
Section: C/ebp Isoforms Are Expressed Differentially and Bind To The mentioning
confidence: 99%